Intoxication-related teenagers' suicide attempts - an analysis of the issue - Sosnowska, Weronika; Brzozowska, Aleksandra; Tchórz, Michał; Tomczyk, Jakub; Więcław, Kacper; Stańko, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction and Aim: Adolescent suicide attempts are a significant clinical and social issue. Often, young people resort to medications, alcohol, or psychoactive substances in their suicide attempts. The aim of this study was to analyze the factors contributing to suicidal behaviors and the characteristics of substances used by adolescents for suicidal purposes. Materials and Methods: In this retrospective study, medical documentation analysis was used. The study included the medical records of 45 individuals up to 18 years of age who were admitted to the Clinical Toxicology-Cardiology Department due to poisoning for the purpose of suicide in the year 2022. Results: The study group consisted of 45 individuals aged 15 to 18 years. Suicide attempts accounted for 37.5% of toxicology hospitalizations in the under 18 age group. The dominant group consisted of females (82.2%) and urban residents (62.2%). Those hospitalized following a suicide attempt primarily used medications, often over-the-counter analgesics. The majority (71.1%) suffered from mental disorders, predominantly depressive disorders (81.2%). Conclusions: Among suicide attempts involving intoxication, those utilizing medications are dominant. A concerning phenomenon is the use of over-the-counter (OTC) medications, commonly considered safe. Girls are particularly vulnerable to emotional difficulties that can lead to suicide. Mental disorders pose a suicidal risk, and patients with such disorders have access to psychiatric medications that can become tools for self-harm.